2011
DOI: 10.1684/abc.2011.0626
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory cryptosporidiosis in two patients with HIV infection in a tertiary care hospital in Morocco

Abstract: Respiratory cryptosporidiosis in two patients with HIV infection in a tertiary care hospital in Morocco Cryptosporidiose respiratoire chez deux patients infectés par le VIH dans un hôpital de soins tertiaire au Maroc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A 1996 review of pulmonary cryptosporidiosis reported only 57 published cases, 4 and few have been reported since. 510 However, a 1995 trial that screened the sputum of AIDS patients with intestinal cryptosporidiosis found that 16% also had Cryptosporidium in sputum samples, 11 and a recent study that used polymerase chain reaction to examine the sputum of HIV-negative children with intestinal cryptosporidiosis found that one-third also had respiratory involvement. 12 These studies indicate that pulmonary cryptosporidiosis may be more common than is widely reported.…”
Section: Discussionmentioning
confidence: 99%
“…A 1996 review of pulmonary cryptosporidiosis reported only 57 published cases, 4 and few have been reported since. 510 However, a 1995 trial that screened the sputum of AIDS patients with intestinal cryptosporidiosis found that 16% also had Cryptosporidium in sputum samples, 11 and a recent study that used polymerase chain reaction to examine the sputum of HIV-negative children with intestinal cryptosporidiosis found that one-third also had respiratory involvement. 12 These studies indicate that pulmonary cryptosporidiosis may be more common than is widely reported.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms associated with this route are respiratory (laryngo-tracheitis) and could be accompanied by mild diarrhea. Reports of cryptosporidial infections of the respiratory tract 80 as well as gastric cryptosporidiosis 81 among immune-deficient and immune-competent individuals have indicated that this protozoan is not restricted only to the gastrointestinal tract rather exhibits extraintestinal tropism. Two reports of respiratory cryptosporidiosis, one in an adult 82 and the other in a 10-year-old child, have been reported in India.…”
Section: Food-and Water-borne and Respiratory Cryptosporidiosismentioning
confidence: 99%
“…The estimated prevalence rate of adults (aged 15–49 years) living with HIV infection is one of the lowest in the world (less than 0.1%). In Morocco, although no data are available concerning the incidence of cryptosporidiosis in HIV-infected patients, two respiratory cryptosporidiosis cases were reported in this population under high active antiretroviral therapy (HAART) [ 10 ]. Algeria has a sustained low-level epidemic (prevalence in the general population in Algeria is less than 0.1%), and rates are higher among migrant and mobile populations, according to the national plan to combat sexually transmitted infections/HIV/AIDS for 2020–2024 issued by the Ministry of Health, Hospitals and Population Reform of Algeria.…”
Section: Introductionmentioning
confidence: 99%